TO INCREASE THE EFFECTIVENESS OF TRAINING IN THE TRAINING OF SPECIALISTS OF ALTERNATIVE ENERGY SOURCES (SOLAR AND WIND ENERGY)ON THE BASIS OF INNOVATIVE TECHNOLOGIES OF EDUCATION - Yuldashev Farrukhjon Murod ogli; Yuldashev Javohir Murod ogli (Galaxy International Interdisciplinary Research Journal, 2021)
In this article, the innovative forms of training (training, round table, interactive lecture, interactive lecture, videoconference, virtual lecture, virtual lecture, etc.) are developed to improve the effectiveness of training specialists of alternative energy sources (solar and wind energy) on the basis of innovative technologies of Education.) such issues will find their own solution.